STRENGTHENING MENTAL AND SPIRITUAL WITH COUNSELING BASED ON THE QURAN AND HADITH - Sadiyah, Jamilatus; Fitriyani , Nina (Universitas Islam Negeri Mataram, 2025)
Mental and spiritual well-being is essential in life, especially amidst thepressures of modern times. Many people experience stress, anxiety,and depression, but often struggle to find solutions that align withtheir religious values. Counselling based on the Quran and Hadithoffers an approach that integrates mental and spiritual dimensions,utilising Islamic teachings to achieve holistic life balance.Through prayer, remembrance of Allah, and understanding Quranicverses and Hadith, individuals can find inner peace and meaningfulways to address life's problems. Islamic counselling strengthensmental and spiritual well-being, providing effective long-termsolutions. Based on literature reviews and individual testimonials,counselling based on the Quran and Hadith has proven to offersignificant benefits, not only in addressing mental issues but also instrengthening the relationship with Allah and building solidaritywithin the Muslim community.This approach helps individuals face life's challenges more calmly andwisely. Islamic counselling is not just a temporary solution, but also away to deepen faith and achieve true tranquillity. By integratingIslamic principles into therapy, Islamic counselling becomes a suitablealternative for those seeking solutions in line with their religiousbeliefs.